Comments on "Trial summary on the comparison of various non-aflatoxigenic strains of Aspergillus flavus on Mycotoxin levels and yield in maize" by M.S. Molo, et al. Agron. J. 111:942-946 (2019) - Ortega Beltran, A.; Bandyopadhyay, Ranajit (Wiley, 2019)
Dear Editor We read with great interest the recently published study in Agronomy Journal in which use of native Aspergillus flavus strains as biocontrol agents was described as an effective strategy to limit aflatoxin contamination of maize (Molo et al., 34). The Molo et al. (34) study was conducted during a single season, in a single field of a research station in the state of North Carolina. Yet, the authors, in our opinion, make nonrigorous comments and conclusions related to this important biocontrol technology. We also have read online news articles—one in the web portal of the American Society of Agronomy—related to Molo et al. (34) in which it is implied that the use of native atoxigenic strains to limit crop aflatoxin content is a novel concept (Chakravorty, 13; Fisk, 25). Merriam-Webster Dictionary defines novel as, “new and not resembling something formerly known or used”. The concept of native atoxigenic strains to limit crop aflatoxin content was introduced in the late 1980s (Cole and Cotty, 14; Cotty, 15) and even discussed in a 2010 article (Burness Communications, 11) by one web portal also providing commentary on Molo et al. (34) (American Society of Agronomy, 3). Molo et al. (34) and the online news commentaries on the article provide readers inaccurate interpretations of the status of aflatoxin biocontrol technology across the globe. The article leaves the impression that use of native atoxigenic strains is new, whereas this concept is one of the bases of aflatoxin management through biocontrol with atoxigenic A. flavus active ingredients (Mehl et al., 33) and use of native atoxigenic strains is mentioned in the title of a patent issued in 1992 by the US government (Cotty, 16). The first reports of native atoxigenic strain efficacy in cotton (Cotty, 17, 18) and maize (Brown et al., 10) were made almost three decades ago, and benefits of using native atoxigenic strains mentioned in the news commentaries in terms of soil and climate adaptation are concepts stressed in several publications (Cotty, 20; Probst et al., 42; Mehl et al., 33; Atehnkeng et al., 5, 4; Bandyopadhyay et al., 8). Results of Molo et al. (34) should be considered as a preliminary indication that native atoxigenic strains are also beneficial for limiting maize aflatoxin content in North Carolina.